Where are the children now? - Clark, Mary Higgins; Burke, Alafair (2023)
"A lawyer turned successful podcaster, Melissa has recently married a man whose first wife died tragically, leaving him and their young daughter, Riley, behind. While Melissa and her brother, Mike, help their mom, Nancy, relocate from Cape Cod to the equally idyllic Hamptons, Melissa's new stepdaughter goes missing. Drawing on the experience of their own abduction, Melissa and Mike race to find Riley to save her from the trauma they still struggle with--or worse"--
Keywords: Missing children -- Fiction; Hamptons (N.Y.) -- Fiction